INSPIRASI FILM “DREAM” DALAM PERWUJUDAN FABRIC MANIPULATION DI BIDANG FASHION - Zahro, Siti; Nadyne Feliciona Towoliu, Steffie; Mustikasari, Hany (Universitas Negeri Surabaya, 2025)
Currently, humans are increasingly moving towards individualism. This is due to the influence of technological developments and trust issues in society. Therefore, relationships between humans need to be built and maintained in social life for the sustainability of interdependent and bound life. Furthermore, the idea of ​​this research was inspired by the film